Diamond sources of the Juína region, Amazonian craton: textural and mineral chemical characteristics of Kimberley-type pyroclastic kimberlites - CABRAL NETO, Izaac (2023)
Juína is the second-largest diamond-producing municipality in Brazil and is globally known for its outstanding sublithospheric diamond occurrences in both placer and kimberlite-hosted deposits. However, the scarcity of petrological data for Juína kimberlite pipes hampers understanding the nature and mantle source of these primary diamond sources in this region. Here, we present a textural and mineralogical study of ten kimberlite pipes from the Juína area. Based on petrographic features and mineral compositions, we interpret the studied Juína pipes as archetypal kimberlites with pyroclastic emplacement styles filled with resedimented volcaniclastic kimberlite and Kimberley-type pyroclastic kimberlite variants. The composition and texture of the magmatic phases, particularly spinel and phlogopite, suggest crystallisation from kimberlite sensu stricto magmas. The presence of high-Na eclogitic garnets and the absence of high-Cr low-Ca G10 garnets within the mantle xenocryst suite suggest the likelihood of eclogitic diamonds among Juína's lithospheric diamond populations. The Zr and Y contents, Ti/Eu and Zr/Hf ratios in the peridotite garnets, and Zr contents, Ca/Al, LaN/YbN (primitive-mantle normalised), Ti/Eu, and Zr/Hf ratios in the clinopyroxenes suggest a solid connection to kimberlite melt-related mantle metasomatism. Thermobarometry calculations indicate a relatively narrow stability window (825–936 oC and 32–36 kbar) for lithospheric diamonds in the Juína region. Our findings have important implications for regional diamond exploration programs, shedding light on the primary sources of Juína's diamonds and contributing to understanding the deep geological processes in the underlying lithospheric mantle beneath the Amazonian craton.